2 hours! because, 12 plus 3 is 15 & 15 times 2 equals 30
Answer:
Equation of the circle (x-3)²+(y-5)²=(6.4)²
x² -6x +9 +y² -10y +25 = 40.96
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given endpoints of diameter P(−2, 1) and Q(8, 9)
Centre of circle = midpoint of diameter
Centre = 
Centre (h, k) = (3 , 5)
<u><em>Step(ii):-</em></u>
The distance of two end points
PQ = 

PQ = √164 = 12.8
Diameter d = 2r
radius r = d/2
Radius r = 6.4
<u><em>Final answer:-</em></u>
Equation of the circle
(x-h)²+(y-k)² = r²
(x-3)²+(y-5)²=(6.4)²
x² -6x +9 +y² -10y +25 = 40.96
x² -6x +y² -10y = 40.96-34
x² -6x +y² -10y -7= 0
<span>
Let's analyze Hannah's work, step-by-step, to see if she made any mistakes. </span>In Step 1, Hannah wrote

<span> as the sum of two separate derivatives </span>

<span>using the </span><span>sum rule.
</span>
This step is perfectly fine. In Step 2,

was kept as it is, and

was rewritten as

using the constant rule.Indeed, according to the constant rule, the derivative of a constant number is equal to zero.
This step is perfectly fine. In Step 3,

was rewritten as

supposedly using the constant multiple rule.
The problem is that according to the constant multiple rule,

should be rewritten as

and not as

.
<span>
Therefore, Hannah made a mistake in this step.</span>